Cyst‐based toxicity tests. VII. Evaluation of the 1‐h enzymatic inhibition test (fluotox) with Artemia nauplii - Espiritu, Emilyn Q (Archīum Ateneo, 1995)
The newly developed 1‐h enzymatic inhibition bioassay (Fluotox) was applied to toxicity testing with the larvae of the brine shrimp Artemia. The method consists of visual observation of in vivo inhibition of an enzymatic process using a fluorigenic enzyme substrate. The 1‐h Fluotox test and the conventional 24‐ and 48‐h LC50 toxicity tests were conducted in parallel on 8 different organic and inorganic chemicals. A good correlation was found between the 1‐h EC50 and the 24‐ and 48‐h LC50 data with r 2 s of 0.94 and 0.93 for each respective regression. Addition of the enzyme substrate did not influence the toxicity of the chemicals in the 24‐ and 48‐h tests. The repeatability of the Fluotox test compares favorably with that of the conventional 24‐h acute test; coefficients of variation (CV) ranged from 8 to 34% and from 1 to 39%, respectively. Investigations on the applicability of the Fluotox procedure for testing in brackish waters revealed that lowering the salinity from 35 to 15 ppt did not affect the fluorescence and mortality responses in the controls. The same decrease in salinity had no significant influence on the 1‐h EC50s except for NaLS and acetic acid. The ratio between the 1‐h EC50s at 35 and 15 ppt varied from 0.46 to 2.18 depending on the chemical. However, the same decrease in salinity significantly influenced (p < 0.05) the 24‐h LC50s (except NaPCP) and the 48‐h LC50 (except formaldehyde). In general, the ratio of the LC50 values obtained at 35 and 15 ppt varied from 0.30 to 2.21 and from 0.48 to 2.53 for the 24‐ and 48‐h exposures, respectively. In view of several inherent advantages such as rapidity, experimental simplicity, low cost of performance, and the use of dry cysts as biological starting material (which eliminates the maintenance of live stock culture) the 1‐h Artemia Fluotox test offers promising potential for numerous ecotoxicological applications. © by John Wiley & Sons, Inc.